Complete Genome Sequence of Enterobacter roggenkampii ED5, a Nitrogen Fixing Plant Growth Promoting Endophytic Bacterium With Biocontrol and Stress Tolerance Properties, Isolated From Sugarcane Root - Guo, Dao-Jun; Singh, Rajesh Kumar; Singh, Pratiksha; Li, Dong-Ping; Sharma, Anjney; Xing, Yong-Xiu; Song, Xiu-Peng; Yang, Li-Tao; Li, Yang-Rui (Frontiers in Microbiology, 2020)
Sugarcane is the leading economic crop in China, requires huge quantities of nitrogen in the preliminary plant growth stages. However, the use of an enormous amount of nitrogen fertilizer increases the production price, and have detrimental results on the environment, causes severe soil and water pollution. In this study, a total of 175 endophytic strains were obtained from the sugarcane roots, belonging to five different species i.e., Saccharum officinarum, S. barberi, S. robustum, S. spontaneum, and S. sinense. Among these, only 23 Enterobacter strains were chosen based on nitrogen fixation, PGP traits, hydrolytic enzymes production, and antifungal activities. Also, all selected strains were showed diverse growth range under different stress conditions i.e., pH (5-10), temperature (20-45 ºC), and NaCl (7-12%) and 14 strains confirmed positive nifH, and 12 strains for acdS gene amplification, suggested that these strains could fix nitrogen along with stress tolerance properties. Out of 23 selected strains, E. roggenkampii ED5 was the most potent strain. Hence, this strain was further selected for comprehensive genome analysis, which includes a genome size of 4,702,851 bp and 56.05% of the average G+C content. Genome annotations estimated 4349 protein-coding with 83 tRNA and 25 rRNA genes. The CDSs number allocated to the KEGG, COG, and GO database were 2839, 4028, and 2949. We recognized a total set of genes that are possibly concerned with ACC deaminase activity, siderophores and plant hormones production, nitrogen and phosphate metabolism, symbiosis, root colonization, biofilm formation, sulfur assimilation and metabolism, along with resistance response towards a range of biotic and abiotic stresses. E. roggenkampii ED5 strain was also a proficient colonizer in sugarcane (variety GT11) and enhanced growth of sugarcane under the greenhouse. To the best of our knowledge, this is the first information on the whole-genome sequence study of endophytic E. roggenkampii ED5 bacterium associated with sugarcane root. And, our findings proposed that identification of predicted genes and metabolic pathways might describe this strain an ecofriendly bioresource to promote sugarcane growth by several mechanisms of actions under multi-stresses.